(untitled) (International Journal of Physiology, 2020)
Introduction: Maternal mortality is unacceptably high. About 295 000 women died during and following pregnancy and childbirth in 2017. The vast majority of these deaths (94%) occurred in low-resource settings, and most could have been prevented. Women face high risk of maternal deaths in south Asia and sub Saharan Africa. (1) Aims and Objective: To identify causes of maternal deaths in a tertiary care hospital. Materials and Method: This is a retrospective study conducted in a tertiary level hospital of Bundelkhand Medical College Sagar M.P. in central India. A retrospective case record examined related to maternal mortality in hospital setting. Ethical approval was obtained from Institutional ethical committee. Data was collected in predesigned proforma. Data were analyzed for age, gravidity, trimester of pregnancy, duration of deaths and causes of death. Results: During 1st January 2018 to 31 December 2019, 44 maternal deaths amongst 11944 live births occurred in obstetrics department of Bundelkhand Medical College Sagar M.P. India. Most no. of deaths occurs in age between 21-30 years (86.4%) followed by 31-40 years (6.8%). The maternal mortality ratio (MMR) stood at 368 per lac live births. 31% were primigravida. The leading causes of death were Pre-eclampsia & Eclampsia (34%), Severe Anaemia (20%) and Hepatic encephalopathy (13%). Conclusions: Based on the results we found that hypertensive disorder (Pre-eclampsia & Eclampsia) is an important cause of maternal mortality followed by Severe Anaemia, Hepatic encephalopathy, Septic abortion and postpartum haemorrhage. Maternal mortality is a reflection of the standards of obstetric service and quality of healthcare. The audit of such mortality would help in identifying the problems and prevent recurrence by taking appropriate measures. Hence the present study was conducted at tertiary care hospital to review the maternal deaths and causes of maternal mortality